2022
DOI: 10.37817/mediaabdimas.v1i3.2573
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pengembangan Perangkat Pembelajaran bagi Guru MA Ma’arif Kota Batu di Era Merdeka Belajar

Abstract: Perubahan tren prendidikan pada era merdeka belajar, menuntut guru sebagai garda terdepanpendidikan untuk dapat mengembangkan perangkat pembelajaran yang sesuai. Berdasarkan hasil observasidan wawancara Kepala Sekolah di MA Ma’arif Kota Batu, diketahui bahwa guru masih membutuhkanpelatihan pengembangan perangkat pembelajaran guna mengembangkan kompetensi guru. Oleh karena itu,tim Abdimas berupaya meningkatkan pengetahuan dan komptensi guru dalam pengembangan perangkatpembelajaran di era Merdeka Belajar melalui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…This can improve the effectiveness of teaching as well as have a positive impact on Curriculum implementation (Mapuya, 2021). (Fathani et al, 2022). This is consistent with previous research, which found that holding an inperson consultation and discussion with the teachers involved in the case study can increase their understanding of the Curriculum philosophy, the preparation of teaching devices, and the evaluation process (Fajar et al, 2021).…”
supporting
confidence: 84%
“…This can improve the effectiveness of teaching as well as have a positive impact on Curriculum implementation (Mapuya, 2021). (Fathani et al, 2022). This is consistent with previous research, which found that holding an inperson consultation and discussion with the teachers involved in the case study can increase their understanding of the Curriculum philosophy, the preparation of teaching devices, and the evaluation process (Fajar et al, 2021).…”
supporting
confidence: 84%